Mutations of the CYP1B1 gene in congenital anterior staphylomas - Judaibi,Ramzi Al; Abu-Amero,Khaled K; Morales,Jose; Al Shahwan,Sami; Edward,Deepak P (Clinical Ophthalmology, 2014)
Ramzi Al Judaibi,1 Khaled K Abu-Amero,2,3 Jose Morales,1 Sami Al Shahwan,1 Deepak P Edward1,4 1King Khaled Eye Specialist Hospital, 2Department of Ophthalmology, College of Medicine, King Saud University, Riyadh, Kingdom of Saudi Arabia; 3Department of Ophthalmology, College of Medicine, University of Florida, Jacksonville, FL, USA; 4Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore MD, USA Purpose: Here, we present two patients with congenital anterior staphyloma, with mutations in the CYP1B1 gene. Methods: We reviewed the medical records, including the genetic analysis. Results: Two unrelated patients presented with congenital anterior staphylomas. Both patients showed mutations in the CYP1B1 gene. The first patient, the product of a consanguineous marriage, showed a homozygous misssense mutation g.3987G>A (p.G61E). The second patient had compound heterozygous misssense mutations [g.4160 G>T (p.A119S) and g.8131 C>G (p.L432V)]. Conclusion: CYP1B1 gene mutation may be associated with congenital anterior staphylomas. Keywords: mutation analysis, congenital glaucoma, consanguinity, congenital aphakia